2021
DOI: 10.1093/mnras/stab2027
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mixing treatments on cloud modelling in 3D simulations of hot Jupiters

Abstract: We present results of 3D hydrodynamical simulations of HD209458b including a coupled, radiatively-active cloud model (EddySed). We investigate the role of the mixing by replacing the default convective treatment used in previous works with a more physically relevant mixing treatment (Kzz) based on global circulation. We find that uncertainty in the efficiency of sedimentation through the sedimentation factor fsed plays a larger role in shaping cloud thickness and its radiative feedback on the local gas tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 95 publications
1
37
2
Order By: Relevance
“…Different spectra could have an impact on the energy deposition in the atmosphere, as for Proxima Centauri b (Lefèvre et al 2021). In hot Jupiter cloud studies, the moment formalism is sometimes used in microphysical modeling (Lee et al 2016;Lines et al 2018), allowing the particle number density to be then determined, as well as the different particle size distributions (Christie et al 2021). Charnay et al (2018) showed a strong gravity effect on the chemistry and microphysics and the overall color.…”
Section: Discussionmentioning
confidence: 99%
“…Different spectra could have an impact on the energy deposition in the atmosphere, as for Proxima Centauri b (Lefèvre et al 2021). In hot Jupiter cloud studies, the moment formalism is sometimes used in microphysical modeling (Lee et al 2016;Lines et al 2018), allowing the particle number density to be then determined, as well as the different particle size distributions (Christie et al 2021). Charnay et al (2018) showed a strong gravity effect on the chemistry and microphysics and the overall color.…”
Section: Discussionmentioning
confidence: 99%
“…Different spectra could have an impact on the energy deposition in the atmosphere, as for Proxima Centauri-b (Lefèvre et al, 2021). In hot jupiters cloud studies, the moment formalism is sometimes used in the microphysical modelling (Lee et al, 2016;Lines et al, 2018), allowing the particle number density to be then determine, as well as different particle size distribution Christie et al (2021). Charnay et al (2018) showed a strong gravity effect on the chemistry and microphysics and the overall color.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several 3D climate models include additional physical processes, which are thought to be important for the understanding of exoplanet atmospheres: clouds (Lee et al 2016;Lines et al 2019;Parmentier et al 2021;Roman et al 2021), photochemical hazes (Steinrueck et al 2021), disequilibrium chemistry (Agúndez et al 2014a;Drummond et al 2018b;Mendonça et al 2018a;Baeyens et al 2021), and magnetic fields (Rogers & Showman 2014). Cloud modeling in 3D climate models ranges from detailed kinetic modeling (e.g., Lee et al 2016) to simple but efficient parametrization (e.g., Roman et al 2021;Christie et al 2021).…”
Section: Versatile Fast 3d Gcm With Non-gray Radiative Transfermentioning
confidence: 99%